Design of pilot plant for separation of CO2 from natural gas using permeation membrane - Saidi, Hamdani; Ismail, Ahmad Fauzi; Aziz, Ramlah Abdul; Aton, Ariffin (1992)
Studies on carbon dioxidelmethane mixtures separation using membrane technology are normally camed out using permeation cells utilising a very small membrane area. The application of the data obtained are usually limited to the operating conditions governing the experimental works namely feed flowrates, pressure, temperature and stage cut In this study a pilot plant-sized membrane gas separation system was designed to generate carbon dioxide/methane data which are more reliable for field situation.